Can green credit policy promote greener manufacturing? Empirical evidence from enterprises’ carbon emission intensity - Zhang, Zijing; Li, Bowen; Wang, Jianxiang (Frontiers in Environmental Science, 2025)
This study empirically examines the impact of the Green Credit Guidelines Policy (GCGP) on carbon emission intensity in China’s manufacturing sector. Using a difference-in-differences (DID) model and panel data from A-share listed firms from 2008 to 2023, we treat the issuance of the GCGP in 2012 as a quasi-natural experiment. The results demonstrate that the GCGP significantly reduces the carbon emission intensity of manufacturing enterprises. Further analysis reveals that this effect operates through both macro and micro-level mechanisms. At the macro level, green credit promotes industrial structure upgrading and enhances energy utilization efficiency. At the micro level, it improves investment efficiency and the quality of environmental information disclosure, thereby supporting carbon reduction. Heterogeneity analysis shows that the carbon-reducing effect of green credit is more pronounced in firms with strong internal governance, low financing constraints, and a high degree of digital transformation. Additionally, the policy is more effective in regions with stricter environmental regulations, higher financial development, and a stronger orientation toward economically developed areas. These findings offer important theoretical insights and policy implications, underscoring the role of green finance in achieving low-carbon transformation and supporting sustainable development goals.